2021
DOI: 10.3390/biology10060557
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Atlas of Promoter Expression Reveals Contribution of Transcribed Regulatory Elements to Genetic Control of Disuse-Mediated Atrophy of Skeletal Muscle

Abstract: The prevention of muscle atrophy carries with it clinical significance for the control of increased morbidity and mortality following physical inactivity. While major transcriptional events associated with muscle atrophy-recovery processes are the subject of active research on the gene level, the contribution of non-coding regulatory elements and alternative promoter usage is a major source for both the production of alternative protein products and new insights into the activity of transcription factors. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Yoon et al [ 2 ] revealed that high levels of procollagen C-endopeptidase enhancer 2 (PCOLCE2) in Tonsil-Derived Mesenchymal Stem Cells (TMSCs) were highly effective in potentiating ROS generation in co-cultured differentiated HL-60 (dHL-60) cells through an RNA-seq-based DGEA. By performing CAGE-seq on two types of atrophic rat muscle samples and through a bioinformatics pipeline centred on Transcription Start Site (TSS) analysis, Pintus et al [ 3 ] identified non-coding transcribed regulatory elements controlling the skeletal muscle disuse-mediated atrophy. Otálora-Otálora et al [ 4 ] used a bioinformatics workflow which includes differential expression, and coexpression network and coregulatory network analyses of microarray samples to discover possible unique lung cancer biomarkers, as well as possible common biomarkers in tumours (lung, breast, and leukaemia).…”
mentioning
confidence: 99%
“…Yoon et al [ 2 ] revealed that high levels of procollagen C-endopeptidase enhancer 2 (PCOLCE2) in Tonsil-Derived Mesenchymal Stem Cells (TMSCs) were highly effective in potentiating ROS generation in co-cultured differentiated HL-60 (dHL-60) cells through an RNA-seq-based DGEA. By performing CAGE-seq on two types of atrophic rat muscle samples and through a bioinformatics pipeline centred on Transcription Start Site (TSS) analysis, Pintus et al [ 3 ] identified non-coding transcribed regulatory elements controlling the skeletal muscle disuse-mediated atrophy. Otálora-Otálora et al [ 4 ] used a bioinformatics workflow which includes differential expression, and coexpression network and coregulatory network analyses of microarray samples to discover possible unique lung cancer biomarkers, as well as possible common biomarkers in tumours (lung, breast, and leukaemia).…”
mentioning
confidence: 99%